Coraline hydroponic / Mohammad Danish Haikal Mohd Tamize - Mohd Tamize, Mohammad Danish Haikal (Universiti Teknologi MARA, Kedah, 2024)
Presenting the Coraline Hydroponic Module—a remarkable blend of cutting-edge hydroponic technology and natural aesthetics. Each module is painstakingly made from translucent materials and has intricate branching structures that reflect the beauty of coral reefs, giving it the appearance of a delicate coral formation. This modular system is perfect for indoor areas since it allows you to produce herbs, greens, or ornamental plants without soil. It does this by employing LED illumination and nutrient-rich water solutions to promote healthy growth. Its low-maintenance approach appeals to both rookie gardeners and seasoned aficionados. Its modular design enables for varied combinations, whether integrated into living walls or as standalone installations. With its aquatic charm, the Coraline module not only brightens living and work areas but also represents the direction of visually appealing and ecological hydroponic farming solutions.